2020
DOI: 10.1016/j.breast.2020.09.013
|View full text |Cite
|
Sign up to set email alerts
|

Symptoms in long-term breast cancer survivors: A cross-sectional study in primary care

Abstract: Various long-term symptoms can manifest after breast cancer treatment, but we wanted to clarify whether these are more frequent among long-term breast cancer survivors than matched controls and if they are associated with certain diagnoses. Methods: This was a cross-sectional, population-based study of 350 breast cancer survivors treated with chemo-and/or radiotherapy 5 years (median 10) after diagnosis and 350 women without cancer matched by age and primary care physician. All women completed a questionnaire … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 41 publications
2
9
0
Order By: Relevance
“…These findings regarding depressive symptoms (part of psychological QoL) align with the literature indicating that breast cancer survivors have greater mental health problems than cancer-free controls ( 56 , 71 73 ). The previous qualitative analysis revealed that all women in this sample reported a difficult time pre-diagnosis ( 74 ).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…These findings regarding depressive symptoms (part of psychological QoL) align with the literature indicating that breast cancer survivors have greater mental health problems than cancer-free controls ( 56 , 71 73 ). The previous qualitative analysis revealed that all women in this sample reported a difficult time pre-diagnosis ( 74 ).…”
Section: Discussionsupporting
confidence: 87%
“…These findings regarding depressive symptoms (part of psychological QoL) align with the literature indicating that breast cancer survivors have greater mental health problems than cancer-free controls (56,(71)(72)(73). The previous qualitative analysis FIGURE 4 | CogState computerized cognitive ability test score box plots for the benign (breast lump autopsy), no-chemo (treatment for breast cancer), and chemo (treatment for breast cancer) groups.…”
Section: Discussionsupporting
confidence: 80%
“…Due to younger diagnosis age, lack of social support, physical changes and clinical symptoms caused by treatment, the depression incidence in breast cancer patients is higher than that of other malignant tumor patients. [ 6 , 7 ] Statistics showed that 32.8% of breast cancer patients had depressive symptoms, and 42% of patients with recurrent breast cancer were diagnosed with depression, leading to increased mortality, worse clinical prognosis and quality of life. [ 8 , 9 ] A meta‐analysis showed that depression increases the overall risk of death in breast cancer patients by 30%, breast cancer‐specific mortality by 29%, and the risk of recurrence by 24%.…”
Section: Introductionmentioning
confidence: 99%
“…Motor nerve damage can be manifested as weakness, gait and balance disturbance, and difficulties in fine motor skills[ 5 , 6 ]. Furthermore, automatic nerve damage leads to dizziness, blurred vision, constipation, orthostatic hypotension, and erectile dysfunction[ 7 , 8 ]. CIPN can cause persistent pain, loss of fine sensation, and muscle weakness, leading to disability in severe cases[ 4 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%